Respiratorna fizioterapija pri osebi z okvaro vratne hrbtenjače - Bukovec, Adrijana (Rehabilitacija (Ljubljana), 2015)
Background: The case of respiratory physiotherapy of a quadriplegic individual with spinal cord injury at level of fifth and sixth cervical vertebra is presented. Methods: Patient history was recorded and clinical observation was performed (vital signs, inspection, palpation, percussion, lung sounds auscultation, assessment of thoracic diaphragm strength, assessment of cough, assessment of breathing pattern at fixed diaphragm, assessment of breathing in different positions and quick swallowing evaluation). Spirometry, maximal inspiratory pressure, maximal expiratory pressure, peak cough flow, measurements of chest wall circumference, ventilatory response index for assessment of dyspnoea and test for assessment of speech and breathing coordination were also performed. The respiratory physiotherapy programme involved techniques for prevention of respiratory complications, enhancement of breathing mechanics and inspiratory capacity, improvement of inspiratory strength and inspiratory endurance. The patient was enrolled in a six-month rehabilitation programme; respiratory physiotherapy was performed five times per week. Results: There was an improvement in breathing pattern, spirometry results, inspiratory and expiratory muscle strength, cough effectiveness, thoracic cage mobility and speech and breathing coordination. The use of mechanical insufflation-exufflation also improved the patient's cough strength. An improvement in the patient's inspiratory muscle endurance was also noted. Conclusions: The programme of respiratory physiotherapy was effective. Marked improvement in respiratory function was noted. In more than a year after the injury there were no respiratory complications.
Keywords: dihalne mišice; mechanical insufflator-exufflator; Quadriplegia; respiratorna fizioterapija; Respiratory Muscles; respiratory physiotherapy; tetraplegija